Sport-specific impacts of ball games on adolescent brain function: a network meta-analysis of executive cognitive tasks - Yang Wang; Zixuan Luo; Tongyan Zhang; Muyan Zhang; Leonid Kapilevich; Jiale Wang (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Adolescence represents a sensitive developmental window for brain maturation, particularly for executive functions, which are crucial for goal-directed behavior and long-term mental health. While physical activity is associated with brain health, the potentially differential impacts of specific ball games on executive cognitive processes remain insufficiently examined. Objective This study aims to explore the sport-specific associations of eight commonly investigated ball games, selected from a broad literature base, on adolescent executive function, through a comparative analysis across distinct cognitive domains. Methods A systematic review and network meta-analysis were conducted following searches in PubMed, Embase, Cochrane Library, and Web of Science for studies published between January 2000 and March 2025. Eligible cross-sectional studies assessed executive function using one or more of five validated cognitive tasks: Go/No-Go Task, Stop-Signal Task, Stroop Task, Trail Making Test, and N-back Task. The analysis compared adolescents participating in baseball, handball, tennis, badminton, basketball, volleyball, soccer, or table tennis with non-athlete controls. Reaction time was selected as the primary outcome. Effectiveness rankings were established using surface under the cumulative ranking curve (SUCRA), and network consistency and potential publication bias were evaluated using standard diagnostic plots. Results Thirty-two studies were included. Across all five tasks, adolescents involved in ball sports demonstrated significantly better executive function performance than non-athletes. Relatively higher SUCRA rankings were observed for: table tennis and baseball in the Go/No-Go Task (80.0%, 79.6%), soccer in the Stop-Signal Task (89.3%), volleyball in the Stroop Task (99.1%), table tennis in the Trail Making Test (95.4%), and basketball in the N-back Task (76.2%). However, not all sports were represented across every task, and these rankings should be interpreted with caution. No substantial publication bias was identified. Conclusion Participation in ball games was associated with sport-specific differences in executive function performance among adolescents. These findings highlight potential links between structured physical activity and neurocognitive outcomes, supporting its consideration in youth health promotion strategies aimed at fostering brain development, mental resilience, and lifelong cognitive health. Systematic review registration PROSPERO CRD420251036950.